THE USE OF DUBBING VIDEO METHOD IN TEACHING PRONUNCIATION AT SMAN 3 MAJENE - Djasman, Ulfah Kurnia; Rum, Eka Prabawati; Hijrah (English Language Teaching Methodology, 2024)
This study aims to determine whether or not the dubbing video method can improve students' pronunciation, especially diphthongs in learning English in class XI SMAN 3 Majene. The research method used is quantitative with a pre-experimental design. The researcher gave a pre-test to the students, then the researcher conducted treatment through the dubbing video method, and at the end of the meeting, a post-test was given. The population used in this research were students of class XI at SMAN 3 Majene. The sample of this research was the students of the class XI IPA, which included 26 students using a purposive sampling technique.The results showed that the use of the dubbing video method was significant in improving students' pronunciation, especially diphthongs. This is evidenced by the mean pretest score before treatment of 43.08 and the mean value after being given treatment of 53.46, the percentage increase of 24.09%. After analyzing the results of the pre-test and post-test data, the researcher found that the pronunciation value of the p-value (0.000) is smaller than α (0.05). It was concluded that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. That means there is a significant difference between the pre-test and post-test. Therefore, it can be concluded that the application of the dubbing video method in the learning process provides an increase in pronunciation for students.